Fiddlewood Leafroller, Seagrape Moth (suggested common names) Epicorsia oedipodalis (Guenée, 1854) (Lepidoptera: Ditrysia: Pyraloidea: Pyralidae: Pyraustinae) - William H. Kern (EDIS)
These caterpillars roll up leaves of the host plants and use the rolled leaves as larval retreats and locations for pupal cocoons. Although these leaf-eating pests do no permanent damage, they can completely defoliate fiddlewood, a Florida native that can form a large shrub or small tree. The shrub simply puts out a new flush of leaves. The larvae themselves are valuable food source for baby birds during the spring dry season in Florida. This 4-page fact sheet was written by William H. Kern, and published by the UF Department of Entomology and Nematology, February 2015. (Photo:W.H. Kern, Jr., UF/IFAS/FLREC)